2014
DOI: 10.1159/000362957
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Effects of Adipose Tissue Inflammation Factors on miR-378 Expression and the Underlying Mechanism

Abstract: Background/Aims: Obesity and the related metabolic syndrome have emerged as major public health issues in modern society. miRNAs have been shown to play key roles in regulating obesity-related metabolic syndrome, and some miRNAs regulated by adiponectin were identified as novel targets for controlling adipose tissue inflammation. miR-378 is a candidate target that was shown to be involved in adipose differentiation, mitochondrial metabolism and systemic energy homeostasis. However, little is known about the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 42 publications
1
21
0
1
Order By: Relevance
“…Zhang et al [76] demonstrated that overexpression of miR-378 apparently prevents and treats obesity by activating the muscle pyruvate-phosphoenolpyruvate futile cycle and enhancing lipolysis in adipose tissue. In addition, Jiang et al [80] revealed that miR-378 expression in human adipocytes is induced by adipokines (IL-6, TNFα, leptin, and free fatty acids). Recent experiments provided evidence that obesity induces overexpression of miR-143, which inhibits insulin-stimulated AKT activation leading to impairment of glucose metabolism [81].…”
Section: The Role Of Epigenetics and Developmental Programming In Thementioning
confidence: 99%
“…Zhang et al [76] demonstrated that overexpression of miR-378 apparently prevents and treats obesity by activating the muscle pyruvate-phosphoenolpyruvate futile cycle and enhancing lipolysis in adipose tissue. In addition, Jiang et al [80] revealed that miR-378 expression in human adipocytes is induced by adipokines (IL-6, TNFα, leptin, and free fatty acids). Recent experiments provided evidence that obesity induces overexpression of miR-143, which inhibits insulin-stimulated AKT activation leading to impairment of glucose metabolism [81].…”
Section: The Role Of Epigenetics and Developmental Programming In Thementioning
confidence: 99%
“…It was demonstrated that TNF-α, IL-6, and leptin upregulated miR-378 expression indicating that miR-378 is probably a novel mediator in the development of insulin resistance related to obesity [53]. Also miR-378 was identified to be unregulated through adipokines and cytokines and primarily through sterol-regulatory-element-binding protein (SREBP) and CCAAT/enhancer-binding protein (C/EBP) binding sites in the miR-378 promoter region [54]. Both described inflammatory processes are known to be dysregulated during obesity.…”
Section: Resultsmentioning
confidence: 99%
“…HEK293 cells were transfected with 80 ng luciferase reporter vectors and miR-449a mimics (final concentration, 50nM) using the Lipofectamine 3000 (Invitrogen, CA, USA), according to the manufacturer's protocol. After 24 h, luciferase activities were measured using DualLuciferase Reporter System (Berthold), according to the manufacturer's instructions [28].…”
Section: Dual-luciferase Assaymentioning
confidence: 99%